Modified Transarticular External Skeletal Fixation for Support of Achilles Tenorrhaphy in Four Dogs - de Haan, J. J.; Goring, R. L.; Renberg, C.; Bertrand, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Achilles tendon ruptures in four dogs were treated with tenorrhaphy using a modified Kessler locking loop suture pattern and postoperative immobilization in partial extension of the tibiotarsal joint. The temporary immobilization of the tibiotarsal joint was achieved with a modified transarticular external skeletal fixation (MTESF). After predrilling the bone, the first fixation pin was placed in the distal tibia and the second in the calcaneus; they were connected with medial and lateral connecting bars. This immobilization method was easy to apply and to maintain during the postoperative period. The modified transarticular external skeletal fixation was removed between five and eight weeks after the operation. All four tendons healed, and all of the dogs returned to normal function. Modified transarticular external skeletal fixation is an alternative method of immobilization of the tibiotarsal joint for support of healing Achilles tenorrhaphies in dogs.Achilles tendon ruptures in four dogs were treated with tenorrhaphy and postoperative temporary immobilization of the tibiotarsal joint. The immobilization was achieved using a modified bilateral transarticular external skeletal fixation connecting the distal tibia and the calcaneus. All four tendons healed, and all of the dogs returned to normal function.
Keywords: Achilles tendon; tenorrhaphy; external skeletal fixation